Intellectual reasoning and clinical decision-making criteria of critical care nurses: A qualitative study - Ramezani Badr, F; Nikbakht-e-nasrabadi, A; Parsa Yekta, Z; Taleghani, F (Advances in Nursing & Midwifery, 2010)
Background and aim Nurses make important clinical decisions with a great impact on patient care and their professional performance. Although decision-making is a basic and essential concept of nursing, limited understanding exists regarding the quality of clinical decision-making of critical care nurses and its effective factors. The purpose of this qualitative descriptive study was to explore intellectual reasoning and clinical decision-making criteria of critical care nurses. Material and methods 14 nurses in 4 teachinghospitals affiliated with Tehran University of Medical Sciences participated in the study. Data were collected by in-depth semi-structured interviews. Content analysis was used to analyze the data. The interviews were transcribed verbatim and analyzed concurrently with data collection. Findings In general, 6 main themes emerged.3 related to intellectual reasoning included intuition, recognition of similar situations and hypothesis testing and the other 3concerning criteria ofdecision-making were risk-benefit level, organizational requirements and complementary sources of information. Conclusion The findings provide a deep understanding of critical care nurses’ experiences regarding intellectual reasoning and clinical decision-making criteria. This can be influential in addition to facilitating more efficient decision-makings on improving the outcomes of independent as well as collaborative nursing interventions. Keywords: Clinical decision-making, Nurses, Critical care, Content analysis. *Corresponding Author: Farhad, Ramezanibadr. Dept. of Medical-Surgical Nursing, College of Nursing and Midwifery, Zanjan University of Medical Sciences, Zanjan, Iran. E-mail: ramazanibadr@zums.ac.ir